The Influence Of Perceived Ease Of Use And Security On The Consumptive Behavior Of OVO Users In Medan City - Br Ginting, Chintya Amanda; Adlina , Hafiza (SEAN Institute, 2022)
This study aims to determine the effect of perceived ease of use and security on the consumptive behavior of OVO users in medan cities. The research method uses quantitative research with an associative approach. The population in this study was all OVO users in medan with a sample of 100 respondents where sampling with purposive sampling technique. The primary data used were obtained from respondents through questionnaires distributed with google forms while secondary data were obtained with literature studies. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis test, reliability, classical assumption test, multiple linear regression analysis, and hypothesis test. The results of the study conducted showed that the perceived ease of use (X1) and safety (X2) variables had a significant effect on consumptive behavior. Perceived ease of use and security variables also simultaneously influence consumptive behavior (Y). The coefficient of determination test showed that there was a relationship between perceived ease of use and safety to consumptive behavior with an R value of 0.514.